(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals the commonality of socio-political, socio-economic, judicial-legal reforms in further deepening of democratic reforms and development of civil society. The role of socio-political advertising in forming and improving the active citizenship position of young people is revealed. Also, modern directions of the influence of groups fighting for power in the election processes on the formation of an active citizenship position among young people have been scientifically studied.